PERAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE IPHONE YANG DIMEDIASI OLEH SIKAP (Studi Pada Konsumen Pengguna Iphone di Kabupaten Gianyar) - Swatama, I Gede Agung Adi; Warmika, I Gde Kt (E-Jurnal Manajemen, 2022)
The development of communication technology media in Indonesia is currently increasingly sophisticated in people's lives and cannot be avoided. As more and more people are using communication media in the form of cellphones. The purpose of this study was to explain the influence of lifestyle on purchasing decisions, attitudes towards purchasing decisions, and the role of attitudes in mediating the influence of lifestyle on iPhone smartphone purchasing decisions in Gianyar City. This study used a questionnaire in data collection, the sample used was 190 people. The data analysis technique uses path analysis. The results showed that lifestyle had a positive and significant effect on iPhone purchasing decisions in Gianyar Regency. Lifestyle has a positive and significant effect on the attitudes of Iphone Iphone users in Gianyar Regency. Attitude has a positive and significant effect on iPhone purchasing decisions in Gianyar Regency. Attitudes significantly mediate the relationship between lifestyle and iPhone purchasing decisions in Gianyar Regency. Keywords: Lifestyle, Purchase Decision, Attitude